The determining role of bolus rheology in triggering a swallowing - Chen, Jianshe; Lolivret, Laetitia (Food hydrocolloids, 2011)
Swallowing is the final stage of an eating process. Even though individuals know exactly when and how to swallow, the controlling mechanisms and the determining criteria of bolus swallowing are still not yet clear. One hypothesis is that bolus rheology, i.e. its flow-ability and stretch-ability, determines the triggering of a swallowing and the main aim of this work was to test this hypothesis. A wide range of fluid foods, including 18 commercial products and 10 lab-constituted foods, were examined for easiness of swallowing by a panel of 19 subjects. Oral residence time, defined as the time from the ingestion till the completion of swallowing, was determined for each eating process. It was observed that the oral residence time had a linear relationship with the sensed difficulty of swallowing. That is a food sensed difficult-to-swallow tends to stay longer in the oral cavity. Rheological properties (both shear and stretching flow) of these foods and their simulated boluses (mixture of food and simulated saliva) have also been determined at body temperature. The apparent shear viscosity showed a positive correlation with the sensed difficult of swallowing. However, the stretching behaviour of a fluid food, characterised by the maximum stretching force and the work of stretching showed much improved correlation to the sensory perceived easiness of swallowing. It was concluded that bolus rheology, in particular its extensional stretch-ability, had the most important influence on the ease of swallowing. [Display omitted]